2014
DOI: 10.1080/21665095.2014.973527
|View full text |Cite
|
Sign up to set email alerts
|

Adapting established instruments to build useful food sovereignty indicators

Abstract: The recent context of global food emergency and ecological crisis has increased the relevance of people's struggle for food sovereignty (FSv), which promotes the transformation of the dominant food system and claims 'the right of peoples to healthy and culturally appropriate food produced through ecologically sound and sustainable methods, and their right to define their own food and agriculture systems'. Revisiting two Spanish and Catalan articles developing FSv indicators, this article aims at discussing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
0
30
0
5
Order By: Relevance
“…Reductionist approaches focused on indicators, typically used to evaluate and monitor progress in agriculture, are not appropriate for the holistic nature and complex interactions of agroecology, its political-cultural outcomes and its multifunctional benefits [36,80]. They thus serve to further delegitimize agroecological alternatives rooted in community self-organizing.…”
Section: Disabling Conditionsmentioning
confidence: 99%
“…Reductionist approaches focused on indicators, typically used to evaluate and monitor progress in agriculture, are not appropriate for the holistic nature and complex interactions of agroecology, its political-cultural outcomes and its multifunctional benefits [36,80]. They thus serve to further delegitimize agroecological alternatives rooted in community self-organizing.…”
Section: Disabling Conditionsmentioning
confidence: 99%
“…As components of the FS framework, the literature review identified five conceptual axes and three social variables (Ortega-Cerdà and Rivera-Ferre 2010; Binimelis et al 2014) The conceptual axes were access to resources; production models; agricultural policies; food safety and consumption; transformation (processing); and commercialization. Gender, indigenous population, and the percentage of young people in the population were the three social variables.…”
Section: Results and Discussion A) Development And Validation Of A Sementioning
confidence: 99%
“…Generally speaking, the development of indicators is a three-stage process: (1) defining the components of the concept in question; (2) assigning indicators to each component; and (3) defining scales and threshold values for each indicator (Yegbemey et al 2014;Fraser et al 2006;Badal et al 2011;Mickwitz et al 2006;Binimelis et al 2014).…”
Section: B) Participative Development Of Indicatorsmentioning
confidence: 99%
“…This work has a strong intellectual background that benefits from the work of other researchers investigating food sovereignty, conservation, and cultural resilience (Altieri ; Binimelis et al. ; Graddy , ; Mamen et al. ; Pimbert ; Woodley et al.…”
Section: Climate Change Research—mitigation and Adaptationmentioning
confidence: 99%
“…Yet, Association ANDES and the Potato Park are also focused on documenting cultural resilience and community-based means of protecting and maintaining biodiversity. This work has a strong intellectual background that benefits from the work of other researchers investigating food sovereignty, conservation, and cultural resilience (Altieri 2009;Binimelis et al 2014;Graddy 2013Graddy , 2014Mamen et al 2005;Pimbert 2008;Woodley et al 2006).…”
Section: Climate Change Research-mitigation and Adaptationmentioning
confidence: 99%